AMPK regulation of fatty acid metabolism and mitochondrial biogenesis: Implications for obesity - O’Neill, Hayley M.; Holloway, Graham P.; Steinberg, Gregory R. (Molecular and cellular endocrinology, 2013)
► Skeletal muscle AMPK regulated fatty acid metabolism and mitochondrial biogenesis. ► AMPK, exercise, metabolism and implications in obesity. ► AMPK mediated-adaptations to exercise training. ► AMPK as a potential therapeutic target for obesity-induced insulin resistance. Skeletal muscle plays an important role in regulating whole-body energy expenditure given it is a major site for glucose and lipid oxidation. Obesity and type 2 diabetes are causally linked through their association with skeletal muscle insulin resistance, while conversely exercise is known to improve whole body glucose homeostasis simultaneously with muscle insulin sensitivity. Exercise activates skeletal muscle AMP-activated protein kinase (AMPK). AMPK plays a role in regulating exercise capacity, skeletal muscle mitochondrial content and contraction-stimulated glucose uptake. Skeletal muscle AMPK is also thought to be important for regulating fatty acid metabolism; however, direct genetic evidence in this area is currently lacking. This review will discuss the current paradigms regarding the influence of AMPK in regulating skeletal muscle fatty acid metabolism and mitochondrial biogenesis at rest and during exercise, and highlight the potential implications in the development of insulin resistance.